The relationship of televised violence to the emergence of aggressive behavior at first-year pupils is average - HADJI, Hakima; FADHLI, Fatiha (Social Sciences Journal, 2021)
This study aims to find out the relationship between watching tv violence programs and aggressive behavior in students and knowing their gender differences. In order to do so, a questionnaire was prepared on the quality of children’s favorite violent television programmers and the aggressive behavior scale quoted from the Sun’s Eye scale for researchers (Nabil Hafez& Nader Kassem). The sample of the basic study was 60 pupils (teachers in the first-year average). Several statistical assists (arithmetic average, standard deviation, T-Test test) were used based on the Statistical Calendar for Social Sciences (SPSS). The results of the study showed a correlation between watching violent television shows and aggressive behavior in pupils, with statistically significant differences in favor of males in relation to aggressive behavior.